(untitled) (Physical Education, Health and Social Sciences, 2025)
Peafowls, vital for maintaining insect populations and attracting tourism, susceptible to ectoparasitic infestations that could lead to ecological and economic imbalance. The need for effective parasite control in captive peafowls prompted this investigation into infestation rates in order to improve husbandry practices in wildlife park. A total of 24 specimens were examined in this study which revealed that infested Blue Peafowl had 60% male and 40% female cases while Green Peafowl showed 50% male and 25% female infestation rates and a single male White peafowl was also discovered to be infested. Goniodes pavonis emerged as the main ectoparasite that caused irritation while making birds vulnerable to secondary infections. The levels of infestation were found to be mostly high or moderate in Blue and Green Peafowl but only minimal in White peafowl. The experimental findings confirm that Blue and Green Peafowl face higher parasitic infestation rates from ectoparasites than White peafowl. Organizations must dedicate their resources to creating successful parasite control methods which protect the health of peafowls while preventing potential diseases.